Design of dry-type transformer temperature controller based on internet of things. (28th April 2020) - Leng, Yan; Qi, Jian; Liu, Yepeng; Zhu, Fujian
Based on the application of the internet of things, we design a kind of dry-type transformer temperature controller. In this design, the traditional dry transformer temperature controller is connected to the Cloud which not only increases the Cloud service but also reflects the internet of things. In this paper, a temperature sensor based on STC89C52 microcontroller is introduced regarding hardware structure, program design, and Cloud. It mainly includes PT100 temperature measurement module, digital-analogue conversion module, alarm module, relay module, a digital tube display module, a communication module, and storage module. The Cloud service uses the ONENET Cloud platform to store the temperature state data of the transformer. The controller not only realises the traditional dry-type transformer function but also monitors the temperature state of the transformer and show the fan and alarm's state of the dry transformer temperature controller. The results show that the device is stable and reliable with high accuracy.